Exploratory Study on Social and Environmental Reporting of European Companies in Crises Period - Camelia Iuliana Lungu; Chirata Caraiani; Cornelia Dascalu; Raluca Gina Guse (Journal of Accounting and Management Information Systems (JAMIS), 2011)
The present study promotes arguments for reporting improvement to support stakeholders' confidence and proposes possible policies and strategies for social and environmental reporting, resulting from European companies' activity. We examined the information disclosed in annual reports and corporate social responsibility reports from a sample of the companies listed on the Euronext Stock Exchange over a three-year period. The purpose of the research is to support the idea that the quality of social and environmental information provided by companies is increasing as time passes and in relation to the present economic conditions. We conducted an exploratory study whose results are analysed and discussed in terms of financial and economic evolution within the present world crisis. They give us the possibility to design a new facet of the overall framework for reporting social and environmental information by combining theoretical requirements of the Global Reporting Initiative (GRI) standards with their implementation in the reporting practice of European companies.
Keywords: M10; M14; Q56; 650; social; environmental; reporting; corporate responsibility; companies' practice